High efficiency arrays of polymer solar cells fabricated by spray‐coating in air. (15th August 2015) - Zhang, Yiwei; Griffin, Jonathan; Scarratt, Nicholas W.; Wang, Tao; Lidzey, David G.
Abstract: We present bulk heterojunction organic solar cells fabricated by spray‐casting both the PEDOT:PSS hole‐transport layer (HTL) and active PBDTTT‐EFT:PC71 BM layers in air. Devices were fabricated in a (6 × 6) array across a large‐area substrate (25 cm 2 ) with each pixel having an active area of 6.45 mm 2 . We show that the film uniformity and operational homogeneity of the devices are excellent. The champion device with spray cast active layer on spin cast PEDOT:PSS had an power conversion efficiency (PCE) of 8.75%, and the best device with spray cast active layer and PEDOT:PSS had a PCE of 8.06%. The impacts of air and light exposure of the active layer on device performance are investigated and found to be detrimental. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : High efficiency arrays of polymer solar cells are fabricated by spray‐coating the photoactive and/or PEDOT:PSS layers in air. Devices were fabricated in a 6 × 6 array across a 5 × 5 cm 2 substrate with each pixel having an active area of 6.45 mm 2 . The champion device with spray cast active layer on spin cast PEDOT:PSS had a PCE of 8.75%, and the best device with spray cast active layer and PEDOT:PSS had a PCE of 8.06%.